Corporate social responsibility in Egypt: A study on the current practice, challenges, and potentials - Refaat, Sara (AUC Knowledge Fountain, 2014)
Corporate Social Responsibility (CSR) has gained momentum in Egypt throughout the past decade, yet very little empirical research was conducted on CSR practice in Egypt. This study provides an in-depth understanding of why and how is CSR practiced in Egypt, the challenges faced, and how CSR practice can improve in general. The study presents a series of contextualized and tailor made recommendations for using CSR as an agent of good development. To serve the purpose of this study a series of qualitative in-depth interviews were conducted with thirteen members of the CSR community in Egypt. Data collected from interviews exposed a different reality of CSR practice than the one offered by literature. There is a substantive gap between Western CSR theory and practice, and what is actually happening on the ground in Egypt. For instance, members of the CSR community believe that the philanthropic side of CSR was practiced in Egypt centuries ago by both individuals and businessmen mainly for religious purposes. CSR in Egypt is perceived as a long-standing charitable, informal, paternalistic, voluntary practice, associated with religious beliefs. On the other hand, the modern, secular, and corporate concept of CSR emerged in Egypt in the early 2000, thanks to Multinational Enterprises (MNEs) who introduced the concept in Egypt. Interviews also revealed several flaws in the current practice such as CSR being used primarily as a Public Relations (PR) and marketing tool, the lack of a CSR partnership model, and the lack of a CSR vision. The study ends with a series of recommendations. Recommendations suggested by interviewees include greater cooperation between different stakeholders, more research on CSR practice, and finally, investing less in charitable activities, and more in development programs. Recommendations suggested by the researcher include the establishment of a CSR National Council with the mandate of creating a CSR framework and lobbying for CSR policies in Egypt.